Modification of Alkyd with Epoxy and its Application for Paint Part 1: Epoxy Alkyd Ester Manufacturing and some Properties of Paint made from this Ester - Thanh, Nguyen Trung (VNU Journal of Science: Natural Sciences and Technology; Vol 36 No 1, 2020)
The article introduces the modification of alkyd resin by epoxy resin to make epoxy alkyd ester. The study investigated the effects of reflux xylene content, the proportion of the constituents participating in the esterification reaction on the reaction processing and acidity index of the product. The infrared (IR) spectroscopy results confirmed the formation of ester bonds after the reaction. The paper also studied the mechanical properties of paint film based on the synthesized ester epoxy alkyd and compared them with the alkyd paint, the results showed that impact resistance and hardness of the study sample were higher than those of the alkyd paint sample. In addition, investigation, comparison of thermal stability of alkyd paint and epoxy alkyd paint film were also mentioned. Keywords: Epoxy alkyd esters, mechanical properties, thermal endurance, drying time.